Systematic Directivity for Selecting Special Javelin Throw Exercises - Al-lami , W.A. (International Journal of Psychosocial Rehabilitation, 2020)
The study aims to identify the impact of special exercises for javelin players. The study was conducted on a sample of the Iraqi national team consisting of (10) players, and the researcher used the experimental method for (10) weeks at (3) training units per week, and the time of the main part of the daily training unit ranged at a rate of (40-60) minutes. The researcher used the statistical treatments in the SPSS statistical program and concluded the following: The special exercises for javelin throw contributed to flexibility of movement and strength of working muscles.